Stakeholders and performance management systems of small and medium-sized outpatient clinics - Piotr Korneta (Foundations of Management, 2020)
Performance management systems can be divided into those that rely considerably on significant stakeholders and that ignore stakeholders, other than the stockholders and the clients. Decision makers willing to implement and use a performance management system must decide to what extent such system should rely on various stakeholders. In this study, 10 in-depth interviews with representatives possessing significant experience with small and medium-sized outpatient clinics have been employed. The objective of this paper is to study if an efficient performance management system for small and medium-sized outpatient clinics can ignore stakeholders. The results of this study postulate performance management systems, which are not sufficiently rooted in stakeholders, are not likely to be successful for small and medium-sized outpatient clinics. Developed in this article concept acknowledges wider society and indicates significant stakeholders who cannot be ignored. The paper ends with conclusion, limitations, indications for further research, and some managerial implications.
Keywords: I11; M10; M16; 650; stakeholders; performance measurement; performance management system (PMS); healthcare; outpatient clinics; small and medium enterprises (SMEs)